Investigation on genetic control for yield and yield contributing traits in advanced generation of maize (Zea mays L.) - Begum, S; Amiruzzaman, M; Ahmed, A; Omy, SH; Rohman, MM (Bangladesh Journal of Agricultural Research, 2018)
Twenty five cross progeny of maize developed by Plant Breeding Division of BARI were evaluated by determining general combining ability (GCA) and specific combining ability (SCA) effects following line × tester design involving five female lines and five testers for grain yield and other yield contributing traits. Highly significant genotypic variances specified inclusive inconsistency existed among the genotypes. None of the lines showed significant GCA effects for all the characters, but the line Pac-60/S4-3 and Pac-60/S4-9 showed negative GCA effect for days to 50% tasseling and silking which is desirable to develop early variety. Additionally, the line Pac-60/S4-9, Pac-60/S4-18 and Pac-60/S4-21 showed negative GCA effect for plant and ear height which is also desirable to develop dwarf variety. Nevertheless, none of the cross showed significant SCA effect for any character studied, but crosses Pac-60/S4-21×BIL-113, Pac-60/S4-21×Utn/S4-15, Pac-60/S4-18×Utn/S4-8, Pac-60/S4-3×BIL-113, Pac-60/S4-3×Utn/S4-18, Pac-60/S4-9×Utn/S4-15, Pac-60/S4-9×BIL-113 and Pac-60/S4-21×Utn/S4-10 had higher yield with positive SCA effects. However, considering yield data along with lodging percentage, five crosses namely Pac-60/S4-21×BIL-113, Pac-60/S4-21×Utn/S4-15, Pac-60/S4-21×Utn/S4-10 Pac-60/S4-9×Utn/S4-15 and Pac-60/S4-3×BIL-113 showed better performance. Bangladesh J. Agril. Res. 42(4): 715-724, December 2017